Molecular Detection of the fimH Gene and Studying the Effect of apigenin on Colonization Factors for Clinical Isolates of Escherichia coli (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background:Escherichia species, which include E. fergusonii, E. vulneris, E. hermanii, E. blattae, E. albertii, and E. coli, are members of the bacterial family Enterobacteriaceae.One of the most crucial components of E. coli's pathogenicity is adhesion, and the invasion process is thought to begin when the bacteria bind to uroepithelial cells. Numerous E. coli strains express type 1 fimbria (pilus), which is present in more than 95% of E. coli isolates from infections inside and outside the body. For bacteria that live in a variety of settings, including biotic and abiotic surfaces, pili function as highly effective adhesion tools. The distribution of type 1 pili on the surface of UPEC is uniform.Materials and Methods:For this study, (80) samples were gathered from patients with various ailments who visited hospitals in the AL margan Hilla city between July and October 2022. The samples came from individuals of both sexes and of various ages.The patients' ages ranged from 20 to 60.Results:18 E. coli isolates were found in this study among patients with UTI, vaginitis, and wound infections.                    By employing PCR methods, the results revealed that only 14 isolates were positive for the fim H gene.ConclusionMost commonly, urine, vagina, and wounds can be used to isolate Escherichia coli. The fim H gene, which is important for bacterial adhesion, was present in the majority of E. coli isolates. The PCR method is used to find some sticky genes. All E. coli clinical isolates tested positive for colonization factor antigen (CFA). On CFA, epigenine had little impact.